Biocomputing 2017 2016
DOI: 10.1142/9789813207813_0042
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance of Gene Set Analysis on Genome-Wide Transcriptomics Data When Using Gene Activity State Estimates

Abstract: Gene set analysis methods continue to be a popular and powerful method of evaluating genome-wide transcriptomics data. These approach require a priori grouping of genes into biologically meaningful sets, and then conducting downstream analyses at the set (instead of gene) level of analysis. Gene set analysis methods have been shown to yield more powerful statistical conclusions than single-gene analyses due to both reduced multiple testing penalties and potentially larger observed effects due to the aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, many additional refinements are possible including the incorporation of additional biological information into the Bayesian model (e.g., cross-species gene orthology, metabolic pathway information, etc.). Ultimately, these gene activity estimates can be used in multiple downstream applications including gene set analysis [6] and metabolic flux modeling, among others. Software for the methods illustrated here is available as supplemental files to this manuscript and found here: http://www.dordt.edu/statgen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many additional refinements are possible including the incorporation of additional biological information into the Bayesian model (e.g., cross-species gene orthology, metabolic pathway information, etc.). Ultimately, these gene activity estimates can be used in multiple downstream applications including gene set analysis [6] and metabolic flux modeling, among others. Software for the methods illustrated here is available as supplemental files to this manuscript and found here: http://www.dordt.edu/statgen.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous methods, the estimated mixture distribution parameters can be National Science Foundation Grant MCB-1330734 used to yield a posterior probability aij ∈ [0,1], that gene i is active in condition j. Recently, we further demonstrated that use of gene activity estimates outperformed the use of raw expression data when conducting gene-set analysis approaches to test for differential gene expression [6]. The promising results of the MultiMM method, however, are tempered somewhat by at least three significant limitations.…”
Section: Introductionmentioning
confidence: 99%